EPISTEMOLOGI EKONOMI ISLAM DAN MAQASID SYARIAH DALAM KURIKULUM EKONOMI ISLAM DI PERGURUAN TINGGI - Selamat Muliadi (Islam Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2018)
Abstract. The Epistemology of Sharia Economy and Maqasid Sharia in Islamic Economics Curriculum in the Higher Education. The potencies and roles of Universities both Islamic Higher Education (PTA) and Public Higher Education (PTU) in providing human resources through Islamic economic and finance learning development that accommodates the competencies of industries demand. Islamic economic as discipline has foundation of epistemology. The main problem in the development of economic and Islamic finance in Indonesia is still the gap between the needs of industry and graduate from college. This study aims to analyze how epistemology and the development Islamic economic and curriculum structure of Islamic economics in universities that teach Islamic economic and what is effective approach to be applied so that graduates can meet the needs of financial industry Islamic economic. The method used in this study is a content analysis is used to explain the depth of the curriculum of Islamic economic in university. Based on the results of the study found that the difference was the presence of Islamic economic learning system in higher education so that graduates produced by universities that teach Islamic economic is still little that can meet the market needs of Islamic financial industry.